MINAT KONSUMEN DAN STRATEGI PENGEMBANGAN EKOWISATA HUTAN MANGROVE DI KELURAHAN MENTAWIR KABUPATEN PENAJAM PASER UTARA - Rochadi Kristiningrum; Abubakar M. Lahjie; Masjaya -; Syahrir Yusuf (Lambung Mangkurat University-Indonesia, 2020)
This research are (1) know how much the potential and interest of consumers (2) explain the strategy of developing mangrove forest ecotourism in Mentawir Village. Research methods in the form of quantitative and qualitative data accompanied by primary data and secondary data. Data were collected using surveys, questionnaires, literature, documentation and SWOT. Outcome this research showed that transactional interest dominates respondents' answers regarding ecotourism interests in the Mentawir Village. SWOT analysis shows that ecotourism activities in Mentawir Village are in quadrant I (Aggressive Strategy). Alternative activities by building partnerships between the community and stakeholders to increase ecotourism activities in the Mentawir Village; community participation in activities from planning to evaluation and monitoring; increasing the quality of products that are packaged creatively and varied by involving local communities and increasing the empowerment of tourism-aware groups.